Ibn Khaldun's Thoughts on Education Across Era - Khojir Khojir; Sayuri Sayuri (UIN Sultan Aji Muhammad Idris Samarinda, 2021)
Humans are born in ignorance and then humans turn into knowing since humans can distinguish between right and wrong. Humans are distinguished from animals because their minds can develop and can create new things in the civilization of science. This research is a literature review using a qualitative descriptive approach. In Ibn Khaldun's view, humans are thinking animals, humans are also capable of creating civilizations through perseverance. Education is an effort made by humans consciously in order to develop their potential. Education is also aimed at acquiring new rules.